Market leader - Rogers, John (Harlow, 2005)
Market Leader is the definitive business English course, with flexible, up-to-date materials reflecting today¿s dynamic business environment. This four-level series ¿ with a brand-new course for beginning students ¿ develops language skills, expands vocabulary, and increases students¿ grasp of business concepts with: Coverage of relevant business topics, including ethics, globalization, branding, leadership, and innovation. Material drawn from a wide range of respected business sources and supported by language and skills exercises and useful case studies.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Business english,Study and teaching,Tiếng Anh thương mại,Học và dạy